Grammarly in students' self-directed learning for writing skills: Advantages and disadvantages - Astuti, Dwi; Sumarni, Sri (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2023)
Grammarly as an online grammar checker impacted technology development rapidly. This study aimed to look at the benefits and weaknesses of utilizing Grammarly to improve students' self-directed learning, particularly in writing skills. This study used a qualitative literature review. The data were collected from 10 relevant articles on Google Scholar with the keyword